2015
DOI: 10.5056/jnm14120
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Gastric Electrical and Mechanical Activity by Cholinesterases in Mice

Abstract: Background/AimsGastric peristalsis begins in the orad corpus and propagates to the pylorus. Directionality of peristalsis depends upon orderly generation and propagation of electrical slow waves and a frequency gradient between proximal and distal pacemakers. We sought to understand how chronotropic agonists affect coupling between corpus and antrum. Methods Electrophysiological and imaging techniques were used to investigate regulation of gastric slow wave frequency by muscarinic agonists in mice. We also inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 41 publications
4
24
0
Order By: Relevance
“…Lepr db/db tissues also became more depolarized but this effect probably reflected an aphysiological action of carbachol. 32 Consistent with a previous report, 33 these results indicate that increased cholinergic signaling induces greater responses in Lepr db/db antrums than in WT mice. Since cholinergic input is a key determinant of gastric emptying, 10 the observed changes, which involve functions of both smooth muscle cells (electromechanical coupling) and ICCs (electrical pacemaking), 1,2 likely contribute to the accelerated gastric emptying seen in the Lepr db/db mice.…”
Section: Resultssupporting
confidence: 91%
“…Lepr db/db tissues also became more depolarized but this effect probably reflected an aphysiological action of carbachol. 32 Consistent with a previous report, 33 these results indicate that increased cholinergic signaling induces greater responses in Lepr db/db antrums than in WT mice. Since cholinergic input is a key determinant of gastric emptying, 10 the observed changes, which involve functions of both smooth muscle cells (electromechanical coupling) and ICCs (electrical pacemaking), 1,2 likely contribute to the accelerated gastric emptying seen in the Lepr db/db mice.…”
Section: Resultssupporting
confidence: 91%
“…Previous studies have suggested that this close relationship between nerve processes and ICC‐IM tends to restrict overflow of ACh to SMCs as a result of the high expression of AChE by motor neurons (Worth et al . ; Bhetwal et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the paper by Worth et al, 1 concerning the regulation of gastric electrical and mechanical activity by cholinesterases. We congratulate the authors on this interesting study.…”
Section: To the Editormentioning
confidence: 90%
“…[2][3][4][5][6] It is important to present a balanced factual assessment on the validity of extracellular recordings, so that readers and reviewers remain correctly informed about the technique. In the study cited by Worth et al, 1 slow waves could not be recorded in vitro using extracellular electrodes. However, failing to record slow waves in one study does not mean they cannot be recorded generally.…”
Section: To the Editormentioning
confidence: 99%